PERGESERAN LETAK PERMAKAMAN BELANDA DI KOTA SURABAYA DARI ABAD 18 HINGGA AWAL ABAD 20 - Lengkong Sanggar Ginaris (BRIN, 2019)
Abstract One of the remains of the colonial period in Indonesia is the Dutch cemetery. The Dutch cemetery have splendid tombs, western-style decorations and gravestone written in Dutch. Dutch cemeteries can be find in cities such as Surabaya. During colonial period, Surabaya had four Dutch cemeteries in Jembatan Merah, Krembangan, Peneleh and Kembang Kuning. The aim of this study is to determine factors behind the displacement of the Dutch cemetery in Surabaya. The data in this study are including not only historical data (maps of Surabaya in 1787, 1825, 1866, and 1934), but also archives. The remaining observable cemeteries are in Peneleh and Kembang Kuning, because the Dutch cemeteries at Jembatan Merah and Krembangan have been demolished. Data from the observation are then sorted and analyzed to determine the displacement pattern and the factors behind them. The results show that there have been three Dutch cemetery displacements in Surabaya, triggered by three factors: health, unstable ground condition, and land conversion into settlement.